Association between maternal dupilumab exposure and pregnancy outcomes in patients with moderate‐to‐severe atopic dermatitis: A nationwide retrospective cohort study - Avallone, Gianluca; Cavallo, Francesco; Tancredi, Annalisa; Maronese, Carlo A.; Bertello, Martina; Fraghì, Alessandro; Conforti, Claudio; Calabrese, Giulia; Di Nicola, Matteo R.; Oddenino, Giorgio A.; Gargiulo, Luigi; Gori, Niccolò; et al. (Journal of the European Academy of Dermatology and Venereology, 2024)
There is limited epidemiological evidence on outcomes associated with dupilumab exposure during pregnancy; monitoring pregnancy outcomes in large populations is required. To investigate the potential association between exposure to dupilumab in pregnant women with atopic dermatitis and any adverse pregnancy, neonatal, congenital and post-partum outcomes. We performed a multicentre retrospective cohort study across 19 Italian tertiary referral hospital. Childbearing women were eligible if aged 18-49 years and carried out the pregnancy between 1 October 2018 and 1 September 2022. We retrospectively screened records of 5062 patients receiving dupilumab regardless of age and gender, identifying 951 female atopic dermatitis patients of childbearing age, 29 of whom had been exposed to the drug during pregnancy (3%). The median duration of dupilumab treatment prior to conception was 22.5 weeks (range: 3-118). The median time of exposure to the drug during pregnancy was 6 weeks (range: 2-24). All the documented pregnancies were unplanned, and the drug was discontinued in all cases once pregnancy status was reported. The comparison of the study cohort and the control group found no significant drug-associated risk for adverse pregnancy, congenital, neonatal or post-partum outcomes. The absence of a statistically significant effect of exposure on the event was confirmed by bivariate analysis and multivariate analysis adjusted for other confounding factors. This cohort of pregnant patients exposed to dupilumab adds to the existing evidence concerning the safety of biologic agents in pregnancy. No safety issues were identified regarding the primary outcome assessed. In clinical practice, these data provide reassurance in case of dupilumab exposure during the first trimester. However, the continuous use of dupilumab throughout pregnancy warrants further research.